Speed analysis of quartz and hematite particles in a spiral concentrator by PEPT. (15th May 2016) - Boucher, D.; Deng, Z.; Leadbeater, T.W.; Langlois, R.; Waters, K.E.
Highlights: Quartz and hematite tracers were activated with radioisotope 18 F. The tracers were tracked by PEPT inside a spiral concentrator slurry film. Tracer speed was calculated from the time and location data. Speed pattern gives details about the magnitude of the secondary flow. Abstract: Activated quartz and hematite tracers between 1180 and 1700 μm in diameter were tracked in two sections of the first two turns of a spiral concentrator to ascertain information on valuable and gangue particle motion. The tracking took place while the tracer was flowing in a 20% solids by mass iron ore slurry. The direct activation of mineral particles, combined with the use of an adjustable height circular assembly of modular positron emission particle tracking detectors, has made this tracking possible. The tracer particle trajectories and speeds are presented in this paper. An early separation into two streams (concentrate or loss to tailings) can be seen for certain runs of the hematite tracers. Tracers speeds and radial position from the centre of the spiral give more details about the presence of the slurry film's secondary flow in the middle zone of the spiral trough. Particle inward and outward migration speed in this secondary circulation is presented. The speed of this migration is approximately 0.12 m/s inward and 0.15 m/s outward for the set-up used.